Proteolytic processing activates a viral superantigen (The Rockefeller University Press, 1996)
Mouse mammary tumor virus (MMTV) superantigens (vSAg) undergo proteolytic processing at residues that have been demonstrated in vitro to be recognition sites for the endoprotease furin. To examine the role of furin in the presentation of vSAg7 to T cells, the vSAg7 and class II MHC IEk genes were introduced into Chinese Hamster Ovary (CHO) cells (furin-positive) and into a furin-negative CHO variant (FD11). Both transfected cell lines efficiently presented peptide antigen and bacterial superantigens to T cell hybridomas. However, while the furin- positive cells presented vSAg7 well, the furin-negative cells presented poorly. Transient transfection of the furin-negative cells with an expression plasmid containing the furin gene restored the ability to present vSAg7 efficiently. The marginal presentation of vSAg7 observed using the furin-negative transfectants was eliminated after culture with the protease inhibitor leupeptin, suggesting that one or more endoproteases other than furin have a detectable but limited capacity to proteolytically activate vSAg7. Biochemical analyses revealed that vSAg7 was largely unprocessed in the absence of furin. Thus, viral superantigens, unlike bacterial superantigens, require proteolytic processing to activate T cells.